The use of pineapple leaf fibers (PALFs) as reinforcements in composites - Leão, A. L. [UNESP]; Cherian, B. M.; Narine, S.; Souza, S. F.; Sain, M.; Thomas, S. (Elsevier, 2014)
Pineapple leaf fibers (PALFs) can be utilized as fabrics for textile materials and in the manufacture of yarns and handicrafts in many countries. The excellent mechanical properties and environmentally sustainable characteristics exhibited by PALFs have triggered the interest of researchers to use the material as a potential reinforcement in structural and non-structural applications. This chapter reviews the properties and applications of PALFs and their composites, and focuses on PALFs extraction, characterization, modification, fabrication and the properties of PALFs reinforced micro- and nanocomposites.
Keywords: Chemical treatments; Composites; Mechanical strength; PALFs; Reinforcement